Pemetaan Kompetensi Tenaga Farmasi sebagai Fondasi Pengembangan Sumber Daya Manusia di Apotek ABC - Esi Sekar Rini (Universitas Pahlawan Tuanku Tambusai, 2026)
Business growth needs to be supported by planned Human Capital (HC) management. One of its foundations is job analysis and employee competencies, so that work practices can remain consistent as the organization grows. In the context of Apotek ABC, this need is reflected in competency standards that have begun to be recognized, but have not been organized yet into a formal and standardized framework. This study aims to map the current HC condition and develop competency mapping for key roles within the pharmacy as a basis for standardizing informal work practices and competency standards, while also serving as a foundation for HR development in the pharmacy context. This study used a qualitative case study design, with data collected through semi-structured interviews with four informants and internal document review as data triangulation. The analysis shows that the main challenge does not lie in a lack of capability, but in a codification gap, namely competency standards that have been practiced informally but have not yet been organized into a formal framework that can be used collectively. Based on these findings, the mapping was developed into a value-based competency recommendation framework for key roles that support pharmacy operations and HR development. This framework consists of core, functional, and managerial competencies, supported by proficiency levels, a sample competency dictionary, and a role matrix as an initial reference for recruitment, performance appraisal, and training.